2020
DOI: 10.3390/insects11030156
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Weather on the Flight of an Invasive Bark Beetle, Pityophthorus juglandis

Abstract: The walnut twig beetle, Pityophthorus juglandis Blackman (Coleoptera: Scolytidae), vectors the fungus Geosmithia morbida, which has been implicated in thousand cankers disease of walnut. Little is known about the flight behavior of the insect across seasons, or about the variability in its flight patterns with weekly fluctuations in weather. We sampled flying adults weekly over a 142-week period (from 29 August, 2011 to 2 June, 2014) with 12-unit black plastic multiple funnel traps baited with a male-produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Nevertheless, wood MC is not the only abiotic factor likely to limit the potential geographic range of G. morbida and P. juglandis in J. nigra (Kolařík et al, 2011;Sitz et al, 2017). Most importantly, climatic differences may impact the flight activity and survival of P. juglandis (Luna et al, 2013;Hefty et al, 2017Hefty et al, , 2018Chen et al, 2020). Within the native range of black walnut, it is also possible that xerophilic and thermotolerant fungi such as Xylariaceae and Aspergillus spp.…”
Section: Discussion Wood Moisture Fungal Competition and Tcdmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, wood MC is not the only abiotic factor likely to limit the potential geographic range of G. morbida and P. juglandis in J. nigra (Kolařík et al, 2011;Sitz et al, 2017). Most importantly, climatic differences may impact the flight activity and survival of P. juglandis (Luna et al, 2013;Hefty et al, 2017Hefty et al, , 2018Chen et al, 2020). Within the native range of black walnut, it is also possible that xerophilic and thermotolerant fungi such as Xylariaceae and Aspergillus spp.…”
Section: Discussion Wood Moisture Fungal Competition and Tcdmentioning
confidence: 99%
“…Seybold et al, 2019;Moricca et al, 2020). Moreover, the failure of P. juglandis to successfully establish in the native range of J. nigra despite incidental introductions and high host susceptibility may be due to unfavorable conditions for its symbiont (Utley et al, 2013;Moore et al, 2019), in addition to differences in temperature and seasonal precipitation that may affect beetle flight, dispersal, and survival (Luna et al, 2013;Hefty et al, 2017Hefty et al, , 2018Chen et al, 2020).…”
Section: Discussion Wood Moisture Fungal Competition and Tcdmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some of the most important factors affecting WTB presence and its dispersal probability have been clarified (distance from nearest attacked site, attack index, available host index, orchard size and tree species), the role of other variables-such as environmental conditions (e.g., dominant winds) and human-related activities (e.g., main trade routes, volume and type of potentially infected goods)-should be carefully considered to better understand the potential spread of this relatively new invasive pest across Europe and to establish effective containment and local eradication measures. Help in this regard may come from the recent work of Chen et al (2020) presenting the effects of climatic variables (i.e., precipitation, solar radiation, vapor pressure, air temperature, relative humidity and wind speed) on the flight activity of WTB. Considering also the other Italian regions where WTB was found, after its first record in 2013 the insect traveled over 320 km westwards reaching the Piedmont region in 2014 (Bosio and Cooke-McEwen 2018) and about 200 km southwards reaching the Tuscany region in 2018 (Moricca et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The walnut twig beetle, Pityophthorus juglandis is native to the southwestern USA and Mexico but in less than a decade, it has managed to expand northwards to other western and eastern States [ 12 ] and also invade Italy [ 13 ]. As a recent study has shown [ 14 ], P. juglandis captures in pheromone traps increased together with the mean weekly air temperature and decreased as the mean minimum relative humidity increased, evincing a strong dependency on the local temperature and rainfall regime. Indirectly, drought periods manipulate the interaction between carbon allocation and secondary metabolites (a component of plant defense against insects and pathogens) in plants [ 15 ], something that has largely defined the large-scale bark beetle outbreaks which have intensified in the last decades.…”
mentioning
confidence: 97%